Evaluation of New Technologies for Cancer Control Based on Population Trends in Disease Incidence and Mortality - Etzioni, Ruth (Oxford University Press, 2013)
Cancer interventions often disseminate in the population before evidence of their effectiveness is available. Population disease trends provide a natural experiment for assessing the characteristics of the disease and the potential impact of the intervention. We review models for extracting information from population data for use in economic evaluations of cancer screening interventions. We focus particularly on prostate-specific antigen (PSA) screening for prostate cancer and describe approaches that can be used to project the likely costs and benefits of competing screening policies. Results indicate that the lifetime probability of biopsy-detectable prostate cancer is 33%, the chance of clinical diagnosis without screening is 13%, and the average time from onset to clinical diagnosis is 14 years. Less aggressive screening policies that screen less often and use more conservative criteria (e.g., higher PSA thresholds) for biopsy referral may dramatically reduce PSA screening costs with modest impact on benefit.